2014
DOI: 10.1002/gps.4077
|View full text |Cite
|
Sign up to set email alerts
|

Memantine improves goal attainment and reduces caregiver burden in Parkinson's disease with dementia

Abstract: In this study, memantine improved individually set goals and caregiver burden in PDD. This suggests that clinimetric measures such as GAS may be more sensitive than conventional psychometric measures in detecting improvements in people with PDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
0
34
0
2
Order By: Relevance
“…Consistent with previous meta-analyses, memantine was superior to placebo only in terms of impression of change when analyzed as a continuous outcome measure; this advantage was not observed when analyzed as categorical data in terms of improvement or absence of deterioration. Recently published secondary analyses of memantine suggest some statistical advantages of memantine over placebo in relation to aspects of attention, sleep, caregiver burden, aspects of quality of life, and goal attainment (63)(64)(65)(66). For olanzapine and quetiapine, reductions in psychiatric symptoms appear to be limited by high levels of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous meta-analyses, memantine was superior to placebo only in terms of impression of change when analyzed as a continuous outcome measure; this advantage was not observed when analyzed as categorical data in terms of improvement or absence of deterioration. Recently published secondary analyses of memantine suggest some statistical advantages of memantine over placebo in relation to aspects of attention, sleep, caregiver burden, aspects of quality of life, and goal attainment (63)(64)(65)(66). For olanzapine and quetiapine, reductions in psychiatric symptoms appear to be limited by high levels of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Pragmatic, cost-effective and resource sparing approaches

Interventional trials with pragmatic designs and effectiveness goals should take priority over efficacy trials of potentially high-cost interventions requiring complex diagnostic procedures or disease stratification;

Research evaluating resource sparing approaches, such as “task shifting” for dementia diagnosis and care will be important;

Including health economic analyses in clinical and social care research will be important.

6. Impactful work that will make a measurable difference to those affectedIn the first phase, the focus of clinical and social care-based research for dementia should be on projects with proximal benefits for PwD and their families;To ensure the best outcome for PwD and their families, “real world” studies with meaningful outcomes (i.e., “clinically meaningful” and meaningful to the stakeholders) will be key; this could involve inclusion of Patient/Care reported outcomes (PROs/CROs) [[34], [35], [36]];Implementation studies should be considered, particularly those who have interventions or approaches already demonstrated as being effective in other settings;Follow-on studies from small scale feasibility or pilot studies should be encouraged to avoid the trap of repeated small scale studies which do not deliver definitive solutions to support PwD and their families;Increasing the knowledge and skills of the dementia research workforce improvement science and implementation science methods will steer the focus to tangible and sustainable outcomes for the wellbeing of PwD and their families.7. Capacity and capability building inherent in research programs/projects

Models of research methods and delivery training in LMIC for NCD already exist [37] and could provide good models for dementia research;

New project proposals should include capacity and capability building as part of the overall project plan, with allocated funds, clear protocols and measurement and reporting of outcomes;

These efforts could lean on the developing science of capacity strengthening (i.e., The Capacity Research Unit at Liverpool School of Tropical Medicine) and follow important principles, such as (1) the articulation of “Research Capacity Strengthening Plan” which is aligned to the aspirations of the partnering organizations.

8.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure the best outcome for PwD and their families, “real world” studies with meaningful outcomes (i.e., “clinically meaningful” and meaningful to the stakeholders) will be key; this could involve inclusion of Patient/Care reported outcomes (PROs/CROs) [[34], [35], [36]];…”
Section: Methodsmentioning
confidence: 99%
“…A total of 20 clinical trials evaluating the efficacy of interventions in PDD were identified . All of these trials assessed pharmacological treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Mood and behavioral outcome measures are frequently employed in PDD trials (Table ), with the Neuropsychiatric Inventory (NPI) being the most commonly utilized, in 12 studies . The NPI dysphoria subscore demonstrated moderate concurrent validity (r = 0.62) with the Hamilton Rating Scale for Depression when administered to caregivers of patients with all‐cause dementia .…”
Section: Resultsmentioning
confidence: 99%